Persepsi Positif Orang Tua Balita terhadap Minat dalam Penggunakan CheckIT Moms - Ni Nyoman Ayu Desy Sekarini; Putu Irma Pratiwi; Anjar Tri Astuti (Universitas Ngudi waluyo, 2022)
The developmental status of children under five in Indonesia still requires special attention where children who experience general developmental delays are quite high, reaching 5-10%. Various factors that influence child development include nutritional status, family economic status, parental education, and parental stimulation. The role of parents is the most influential thing in development, namely by doing detection and stimulation independently at home. However, many parents feel unable to do so, because of their ignorance and inability. So that a mobile application was developed to detect and stimulate children's development. This study aims to determine the effect of perceived benefits, convenience, security and risk on the interest of parents of toddlers using